2019
DOI: 10.5897/ajfs2019.1829
|View full text |Cite
|
Sign up to set email alerts
|

Oil yields for Allanblackia parviflora (tallow tree) in Ghana: the effects of oil extraction methods, tree morphology and environmental characteristics

Abstract: This study provided understanding of the oil yields from Allanblackia parviflora fruits in Ghana. The study sought patterns of variations in oil yield between 157 trees, 16 communities and 3 ecological zones. Ecological zone and soil properties were considered as surrogates for growing conditions associated with tree and fruit morphology. Kernel and seed oil yields were determined using the manual screw press ranged from 31.3 to 61.8% and 0.2 to 36.8%, respectively. Large variations were observed between indiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 14 publications
(19 reference statements)
0
2
0
Order By: Relevance
“…Nutritional analyses showed that the seeds contained 4.3% protein, 2.0% ash, 5.7% crude fibre and 17.1% carbohydrates, with the moisture content being 3.4%. Additionally, Sefah et al [58] confirmed the moisture content of A. parviflora seeds to be 3.2%. Nutritional values from A. parviflora seeds were compared with those from A. floribunda and other tropical fruit trees such as Vitelaria paradoxa Kotschy and Theobroma cacao L.,1753 and are summarized in Table 2.…”
Section: Chemical Composition Of a Parviflora Seedsmentioning
confidence: 96%
See 1 more Smart Citation
“…Nutritional analyses showed that the seeds contained 4.3% protein, 2.0% ash, 5.7% crude fibre and 17.1% carbohydrates, with the moisture content being 3.4%. Additionally, Sefah et al [58] confirmed the moisture content of A. parviflora seeds to be 3.2%. Nutritional values from A. parviflora seeds were compared with those from A. floribunda and other tropical fruit trees such as Vitelaria paradoxa Kotschy and Theobroma cacao L.,1753 and are summarized in Table 2.…”
Section: Chemical Composition Of a Parviflora Seedsmentioning
confidence: 96%
“…For instance, morphological and genetic diversity assessment using genetic markers have been reported for A. floribunda in Cameroon [24,25] and A. stuhlmannii in Tanzania [25,68]. However, there is very limited knowledge on studies focusing on the genetic diversity of A. parviflora in West Africa using molecular markers even though some work has been done on the morphological aspects in Ghana [4,17,58]. Genetic markers are employed, for instance, for the estimation of differences between natural and domesticated plant populations, gene flow, fingerprinting, genetic structure, and hybridization, and are therefore essential in breeding programmes and development of new varieties [69,70].…”
Section: Morphological and Genetic Diversitymentioning
confidence: 99%